A comparative immunohistochemical study of HBsAg, HBcAg and CD57 in chronic hepatitis B pediatric patients with and without malignant disorders - Gülden DİNİZ and Safiye AKTAŞ and Ragıp ORTAÇ and İsmet ÜNLÜ and Canan VERGİN (Turkish Journal of Gastroenterology, 2019)
-